Accuracy of forensic pathologists in incorporating post‐mortem CT (PMCT) in forensic death investigation. Issue 6 (6th September 2022) - Makino, Yohsuke; Unuma, Kana; Nolte, Kurt B.; Adolphi, Natalie L.
Abstract: Post‐mortem computed tomography (PMCT) is now performed routinely in some medical examiner's offices, and the images are typically interpreted by forensic pathologists. In this study, the question of whether pathologists appropriately identify significant PMCT findings and incorporate them into the death investigation report and the cause and manner of death (COD and MOD) statements was addressed. We retrospectively reviewed 200 cases where PMCT was performed. The cases were divided into four categories: (1) full autopsy without radiology consultation ( n = 77), (2) external exam without radiology consultation ( n = 79), (3) full autopsy with radiology consultation ( n = 26), (4) external exam with radiology consultation ( n = 18). A radiologist (not the consult radiologist) read the PMCT images, and a pathologist (not the case pathologist) reviewed the case pathologist's post‐mortem examination report in tandem to determine any PMCT findings omitted from the report. Omitted findings were classified into error types according to a modified Goldman classification including Major 1: Unrecognized fatal injury or pathology that would change COD and/or MOD, and Major 2: Unrecognized fatal injury or pathology that would not change COD and/or MOD. A total of 13 Major errors were identified (6.5%), and none definitively changed the MOD. All four Major‐1 errors which could change the COD were found in Category 2. Of 9 Major‐2 errors, 2 occurred in Category 1, 6 occurred in Category 2, and 1 occurred in Category 4. In conclusion, forensic pathologists who routinely utilize computed tomography (CT) interpret CT images well enough to reliably certify the COD and MOD.